RETRACTED: Mathematical model of thermal water concentration - Lokarev Alexander; Potapov Vadim; Matveeva Irina; Markova Evgenia; Gryn Svetlana; Zaberezhny Alexey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001